Soil Chemicals from Croftonweed (Ageratina adenophora) Are Phytotoxic. Issue 2 (June 2016) - Yang, Guoqing; Guo, Jiao; Zhu, Xunzhi; Shao, Hua; Gao, Ting
Abstract : Secondary plant metabolites may influence plant–plant interactions and plant invasions. Distinguishing such chemicals requires integrating varying chemical ecology approaches, information on the amounts and persistence of specific chemicals in nature, and measures of effects (e.g., phytotoxicity assays) to judge the importance of the chemicals (e.g., allelochemicals). The invasive plant croftonweed has caused substantial ecological and economic losses in China. We examined contents and degradation of croftonweed chemicals in the soil and their potential phytotoxic effects on conspecific and five allospecific plant species. Soils in which croftonweed was grown had four phytotoxins: DEHP, DBP, DTD, and HHO. All chemicals were detected in croftonweed-invaded soil, with contents ranging from 0.013 (for DEHP) to 0.353 (for DTD) µg g −1 of soil. All four compounds were degraded rapidly in 1 wk. Combinations of the chemicals inhibited seed germination or seedling growth of four of the six plants, including croftonweed itself, at mean contents found in the soil. The putative allelochemicals degraded rapidly in the soil, and the low levels of allelochemicals observed in the soil may be sufficient to affect seed germination and plant growth.